FRI0418 Outcome of the Autoimmune Congenital Heart Block in 45 Babies from Anti-RO/LA (+) Mothers: Results from the Spanish Registry (Rebacc-Geas-Semi). (9th June 2015) - Brito Zeron, P.; Espinosa, G.; Robles, A.; Rosich, P.; Sáez Comet, L.; Capdevila, O.; Vargas, J.A.; Pallarés, L.; Trapiella, L.; González Nieto, J.A.; Martínez Zapico, A.; Rodriguez, M.; et al.
Abstract : Objectives: To analyze the main maternal-fetal characteristics of pregnancies affected by autoimmune congenital heart block (CHB) associated with maternal anti-Ro/La antibodies, the outcomes and management of affected pregnancies with CHB. Methods: The REBACC Spanish Multicenter Registry was created in March 2014. It is integrated by 11 centers with substantial experience in the management of systemic autoimmune diseases. Autoimmune CHB was defined as: a) CHB of any type (I, II or III), fetal endocardial fibroelastosis (EFE) and/or cardiomyopathy, b) cardiac block diagnosed in utero or in the first postpartum month, and c) mothers carrying anti-Ro52, Ro60 and/or La autoantibodies. Results: On January the 15th, 2015, the REBACC Registry included a total of 40 anti-Ro and/or anti-La+ mothers with 45 single pregnancies with CHB. Mean maternal age at the time of first affected pregnancy with CHB was 31.77 years (range: 22-44). Twenty-eight (70%) mothers did not have any autoimmune disease and the remaining 30% had Sjögren syndrome (n=5), SLE (n=5) and undifferentiated disease (n=2). All mothers were anti-Ro60 (+), 13/13 anti-Ro52 (+) and 29/39 (74%) anti-La (+). The mean gestational age at diagnosis of CHB was 23 weeks (range 16-37). AV blocks were of type I in 2 pregnancies (5%), type II in 13 (32.5%) and type III in 24 (60%); 1 had an isolated EFE (2.5%). Therapies used in 26/40 (65%) pregnancies included dexamethasone or betamethasone (n=24), intravenous immunoglobulins (n=5), plasmapheresis (n=3), beta2-adrenergic agonists (n=2), isoproterenol (n=1). A change of block type was seen in 4 (10%) pregnancies: 1 type II regressed to normal sinus rhythm after birth and 2 type II and 1 type I progressed to type III block. Nine pregnancies were interrupted due to bad fetal prognosis (22.5%) and 31 (77.5%) were successfully carried to term. Pacemaker implantation was required in 16 babies (55%), 14 after birth, 1 at 5 years and another at 12 years of age. Of the 30 women who initially did not have any autoimmune disease, 19 (63%) developed a systemic autoimmune disease at the end of the index pregnancy: SS (n=13), SLE (n=5), SS/SLE (n=1). After the index pregnancy, 12 mothers had another pregnancy with 3 (25%) babies affected with CHB: 2 type III AV block and 1 type I AV block. Four mothers subsequently had a third pregnancy, of which, 2 (50%) were affected by type III CHB diagnosed at 23.5 and 20 weeks. One mother had a fourth and firth pregnancy, none affected by CHB. Conclusions: More than half alive-babies with CHB required pacemaker implantation. The recurrence rate of CHB after a first affected baby was of 25% for the second baby, and of 50% for the third baby. Two out of 3 asymptomatic mothers at the time of diagnosis of the index CHB case developed a systemic autoimmune disease (overwhelmingly Sjögren syndrome) at the end of follow-up. Disclosure of Interest: None declared